2009
DOI: 10.1111/j.1525-1314.2008.00808.x
|View full text |Cite
|
Sign up to set email alerts
|

Prograde P–T path of medium‐pressure granulite facies calc‐silicate rocks, Higo metamorphic terrane, central Kyushu, Japan

Abstract: Prograde P-T path of medium-pressure granulite facies calc-silicate rocks, Higo metamorphic terrane, ABSTRACT This paper reports an occurrence of medium-pressure granulite facies calc-silicate rocks intercalated with pelitic gneisses in the Higo metamorphic terrane, central Kyushu, Japan, which is classified as a low-P ⁄ high-T (andalusite-sillimanite type) metamorphic belt. Three equilibrium stages are recognized in the calc-silicate rock based on reaction textures: M1 stage characterized by an assemblage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 42 publications
(165 reference statements)
0
5
0
Order By: Relevance
“…1992, , 1983Obata et al, 1994;, 1996;Osanai et al, 1998Osanai et al, , 2006aMiyazaki, 2004;Maki et al, 2009Maki et al, , 2014 Bt-Ms , Bt , Grt-Bt , Grt-Crd-Bt , Grt-Opx -1 Spr-Spl GASP -3 900 950°C 0.8 GPa Fig. 8d , , 1986;Osanai et al, 1998Osanai et al, , 2006aHamamoto et al, 1999 , Brown, 1998Brown, , 2007Santosh et al, 2011, Santosh and Kusky, 2010Santosh et al, 2011Santosh et al, , 2012 Tsunogae, T. and Santosh, M., 2004, Sapphirine and corundum bearing ultrahigh temperature rocks from the Palghat-Cauvery Shear System, southern India.…”
Section: °C 1 Gpamentioning
confidence: 99%
“…1992, , 1983Obata et al, 1994;, 1996;Osanai et al, 1998Osanai et al, , 2006aMiyazaki, 2004;Maki et al, 2009Maki et al, , 2014 Bt-Ms , Bt , Grt-Bt , Grt-Crd-Bt , Grt-Opx -1 Spr-Spl GASP -3 900 950°C 0.8 GPa Fig. 8d , , 1986;Osanai et al, 1998Osanai et al, , 2006aHamamoto et al, 1999 , Brown, 1998Brown, , 2007Santosh et al, 2011, Santosh and Kusky, 2010Santosh et al, 2011Santosh et al, , 2012 Tsunogae, T. and Santosh, M., 2004, Sapphirine and corundum bearing ultrahigh temperature rocks from the Palghat-Cauvery Shear System, southern India.…”
Section: °C 1 Gpamentioning
confidence: 99%
“…The metamorphic field gradients estimated by Miyazaki (thin solid arrows) and Osanai et al(a dashed arrow) are both low-pressure gradients, typical of andalusite-sillimanite type metamorphism in the sense ofMiyashiro (1961). The medium-P granulite described byMaki et al (2009) represents pressure conditions higher than the above two estimates, but it is a rare example Osanai et al (2006). estimated the prograde path (a dotted arrow) of the D zone gneiss (in their definition), and ascribed it to the effect of intrusion of hornblende gabbro at 250 Ma.…”
mentioning
confidence: 86%
“…Occurrences of garnet-amphibolite (Karakida & Yamamoto, 1982), staurolite-bearing pelitic gneisses (Maki et al, 2004;Osanai, Hamamoto, Maishima, & Kagami, 1998), and kyanite from river sand (Kano & Uruno, 1995) are indicative of medium-P metamorphism. Osanai et al (1998Osanai et al ( , 2006 found sapphirine-bearing granulites ( 0.9 GPa and 950 C) in the western part of the HMR, and Maki, Fukunaga, Nishiyama, and Mori (2009) reported a calc-silicate granulite ( 0.9 GPa and 820 ±160 C) in the eastern part. Maki et al (2014) studied migmatites and associated high-grade pelitic gneisses and estimated the P-T condition as 0.9-1.2 GPa and 800-900 C. Maki et al (2014) considered that some parts of the HMR reached a pressure condition higher than that thought by earlier workers (e.g., Miyazaki, 2004;Obata et al, 1994), implying that the HMR may have experienced a middle to deep crustal condition.…”
Section: Geological Settingmentioning
confidence: 98%
See 1 more Smart Citation
“…The HMC are andalusite‐sillimanite type metamorphic rocks whose metamorphic grade increases toward the south as high as granulite facies, and cut into several blocks by high‐angle faults that trend E–W and NNE–SSW (e.g., Maki et al, 2004; Maki et al, 2009; Miyazaki, 2004; Obata et al, 1994; Osanai et al, 1998; Tsuji, 1967; Yamamoto, 1962). Biotite, muscovite and hornblende K‐Ar and Rb‐Sr ages of the HMC range from 97.9 ± 2.2 Ma to 109.8 ± 2.4 Ma (Hamamoto et al, 1999; Nagakawa et al, 1997; Nakajima et al, 1995; Shibata & Yamamoto, 1965; Yamaguchi & Minamishin, 1986), and most of them are concentrated around 101–107 Ma.…”
Section: Geological Settingsmentioning
confidence: 99%